Efisiensi Operasional dan Dampak Ekonomi Perubahan Regulasi Kapal Wisata Asing: Analisis Perbandingan PM 4 Tahun 2022 dan PM 14 Tahun 2023 - Barata, Fausta Ari; Nachrawi, Gunawan (FOCUS, 2025)
Maritime tourism in Indonesia has great potential to drive economic growth, particularly through the rapidly expanding foreign cruise sector. However, challenges in operational efficiency and bureaucratic licensing procedures have become major obstacles to its management. To address these issues, the Indonesian government introduced Minister of Transportation Regulation (PM) No. PM 14 of 2023 as a revision of PM 4 of 2022. This regulation aims to enhance port accessibility, simplify licensing procedures, and integrate modern navigation technology. This study employs a normative legal research method with a statutory and conceptual approach. Data were collected from primary, secondary, and tertiary legal sources and analyzed qualitatively to assess the implications of the new regulation on the operational efficiency of foreign cruise ships and its economic impact. The findings indicate that regulatory changes improve operational efficiency by digitalizing licensing systems, expanding strategic ports, and implementing the Vessel Traffic Services (VTS) system. Additionally, immigration reforms through the Immigration on Shipping (IoS) program have significantly reduced ship waiting times at ports. From an economic perspective, this regulatory revision has positively impacted the hospitality, transportation, and SME sectors around ports. However, challenges related to port infrastructure and inter-agency coordination still require further attention to ensure the sustainable implementation of this regulation.